STATINS IN MODERN CARDIOLOGY: FROM DISCOVERY EVIDENCE-BASED CARDIOVSCULAR PREVENTION - Shoymardоn Turaev, (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract. Statins stand among the most consequential pharmacological advances of the twentieth century, reshaping the management of dyslipidaemia and the prevention of atherosclerotic cardiovascular disease. Discovered through systematic screening of fungal cultures by Akira Endo in the 1970s, these HMG-CoA reductase inhibitors have evolved across successive generations from naturally derived compounds such as lovastatin and pravastatin to highly potent synthetic agents including atorvastatin, rosuvastatin, and pitavastatin. Landmark trials-the 4S, WOSCOPS, HPS, and TNT studies among them established mortality benefit across the cardiovascular risk spectrum, while the Cholesterol Treatment Trialists' Collaboration meta-analyses confirmed that each 1 mmol/L reduction in low-density lipoprotein cholesterol (LDL-C) lowers the risk of major vascular events by approximately 22%. Residual cardiovascular risk, statin intolerance, and the limitations of monotherapy in familial hypercholesterolaemia subsequently drove the development of ezetimibe, PCSK9 inhibitors, bempedoic acid, and RNA-based therapeutics. This review traces the historical trajectory of statin research, examines the mechanistic basis of their cardioprotective effects, and situates their role within contemporary evidence-based guidelines.